2023
DOI: 10.1038/s41467-023-36975-2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering zero modes in transformable mechanical metamaterials

Abstract: In the field of flexible metamaterial design, harnessing zero modes plays a key part in enabling reconfigurable elastic properties of the metamaterial with unconventional characteristics. However, only quantitative enhancement of certain properties succeeds in most cases rather than qualitative transformation of the metamaterials’ states or/and functionalities, due to the lack of systematic designs on the corresponding zero modes. Here, we propose a 3D metamaterial with engineered zero modes, and experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Recently, Zhang and co‐workers reported that charge transfer states could be effectively formed in heterostructures of RPP prepared by mixing PEA 2 PbI 4 :PEA 2 SnI 4 crystal. [ 32 ] It is envisaged that the domains of PEA 2 SnI 4 and PEA 2 PbI 4 may occur because the tin and lead compounds have different Gibbs free energies of formation leading to the heterostructures. [ 48–50 ] In this picture, low‐energy luminescence would stem from a charge‐transfer state formed by electron–hole coupling between two chemically different domains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Zhang and co‐workers reported that charge transfer states could be effectively formed in heterostructures of RPP prepared by mixing PEA 2 PbI 4 :PEA 2 SnI 4 crystal. [ 32 ] It is envisaged that the domains of PEA 2 SnI 4 and PEA 2 PbI 4 may occur because the tin and lead compounds have different Gibbs free energies of formation leading to the heterostructures. [ 48–50 ] In this picture, low‐energy luminescence would stem from a charge‐transfer state formed by electron–hole coupling between two chemically different domains.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14,15,31 ] Recently, broadband emissions from mixed divalent metal 2D perovskites have been reported. [ 25,29,32,33 ] Tin (II) has been considered the most suitable candidate for Pb 2+ replacement because of their similar electronic states with lone‐pair orbitals. [ 34–39 ] Therefore, the substitution of Pb 2+ by Sn 2+ is expected to give rise to a minimal perturbation in the lattice structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Conventional metamaterials have fixed unit cell geometries and, accordingly, fixed properties, which limits their applicability. In response, active metamaterials have emerged, which can transform between preprogrammed shapes when subjected to external stimuli, such as mechanical loads, [29][30][31][32] heat, [33][34][35][36] electrical currents, [37][38][39][40] or magnetic fields. [41][42][43][44] These shape transformations often involve internal deformations of the unit cells, which also change the area density and the overall dimensions of the metamaterial.…”
Section: Acousticmentioning
confidence: 99%
“…Metamaterials with tunable mechanical properties [11][12][13][14] , in particular having a rich dynamical behavior [15][16][17][18][19][20][21][22] or exhibiting non-reciprocity 23,24 , are extremely attractive for numerous applications, such as control of the propagation of acoustic and elastic waves [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Beyond the homogenization limit, the idea of dynamic shear, bulk, or mass density is commonly used and accepted for waves 41 .…”
Section: Introductionmentioning
confidence: 99%